INDONESIAN TWITTER USER NATIONALISM DISCOURSE: #INDONESIAUNITE CASE STUDY - Ibnu Nadzir Daraini (Widyariset, 2013)
Social networking sites, is one of the new forms of communication media that have an impact on changing modes of human interaction. One of the social movement-based social networking site in Indonesia is #IndonesiaUnite. This movement began as an effort to show the Twitter users in a positive representation of Indonesia after the bombing. In its development, this movement turned into a collective movement that construct the ideas of nationalism. This paper aims to understand the construction process of nationalism discourse that emerged from the #IndonesiaUnite movement. In addition, this study also attempts to understand the role of social networking sites in the spread of the discourse. In order to answer that questions, discourse analysis is utilized as an analysis method. It turns out that social network sites affecting discourse to spread rapidly. It is caused by social network features that allows its user to see the discourse construction process.